Pengaruh Penggunaan Gadget terhadap Kecerdasan Emosional dan Akhlak Peserta Didik di SMP Islam Terpadu Nurul Ilmi - M Nanda Azhari; Amiruddin Siahaan; Salminawati Salminawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The purpose of this study was to determine the effect of using gadgets on emotional intelligence and morals of students during the Covid 19 period at SMP IT Nurul Ilmi Medan. The research method used is the Quantitative Research Method. The population of this study were students of class VII, VIII and class IX, which consisted of 76 students. The data collection instrument is a questionnaire. The results showed: (1) There is an influence between Gadget Use and Emotional Intelligence because the value of tcount > ttable is 2.514 > 1.99167. Likewise in the F test (Simultaneous) on the variable Gadget Use with Emotional Intelligence it was found that Fcount = 6.321 and with a significance level of 0.014 <0.05. (2) There is an influence between the use of gadgets and morals because the value of tcount > ttable is 9.087 > 1.99167. Furthermore, in the F test (Simultaneous) on the variable Use of Gadgets with Morals, it was found that Fcount = 82.571 and with a significance level of 0.001 <0.05. (3) Based on the results of the analysis in this study by testing the hypothesis using the t test and f test, it can be concluded that there is an effect of the use of Gadgets on the Emotional Intelligence and Morals of students during the Covid 19 period at SMP IT Nurul Ilmi Medan. This can be seen from the t test between Gadget Use and Emotional Intelligence with a tcount > ttable, namely 2.514 > 1.99167. Likewise in the t test between Gadget Use and Morals with a value of tcount > ttable, namely 9.087 > 1.99167. Likewise in the F test (Simultaneous) on the variable Use of Gadgets with Emotional Intelligence it was found that Fcount = 6.321 and with a significance level of 0.014 <0.05 and then in the F test (Simultaneous) on the variable Use of Gadgets with Morals it was found that Fcount = 82.571 and with a significance level of 0.001 <0.05.